Strategi Peningkatan Daya Saing Usaha Santi Batik di Betungan Kota Bengkulu melalui Inovasi Produk dan Penguatan Pemasaran - Nurrahma Hidaya; Reva Agustia; Eta Arisa; Al-Yesi Fitri Rahayu; Uswatun Hasanah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting regional economic development, particularly in culture-based creative industries. Santi Batik Betungan in Bengkulu City is one of the MSMEs that develops Batik Besurek as a regional flagship product with both cultural and economic value. However, the business faces several challenges, particularly in product promotion, digital marketing, and the utilization of supporting technologies. This community service activity aimed to strengthen business capacity through a mentoring program focusing on product promotion, digital marketing, education on the use of digital payment systems (QRIS), and the socialization of Batik Besurek to the community. The activities were carried out through observation, interviews, mentoring, educational sessions, and documentation. The results indicate that the mentoring program successfully improved business visibility, expanded product promotion through digital media, and enhanced the partner’s understanding of business management and the utilization of technology in business operations. In addition, the socialization of Batik Besurek contributed to the preservation of local culture and increased public awareness of Bengkulu’s traditional batik products. This activity demonstrates that collaboration between universities and MSMEs can serve as an effective form of community empowerment in supporting business development, preserving local culture, and enhancing the competitiveness of MSMEs in a sustainable manner.